Deciphering paleoclimatic signals: Organic carbon isotope signatures in terrestrial higher plants and loess from the Iranian Loess Plateau - Qiang Wang; Yining Tang; Jiamei Lei; Mi Wang; Haichao Xie; Xiangfeng Tang; Farhad Khormali; Davlatkhudzha Murodov; Xin Wang (Quaternary Science Reviews, 2026)

1-MCP pretreatment combined with SO2 preservation pad delays postharvest senescence and softening of ‘Shine Muscat’ grapes by regulating cell-wall metabolism and antioxidant activity - Chunrui Chen; Peili Lan; Zijia Nan; Chenguang Li; Xiaoyu Jia; Yanfang Pan; Yining Xia; Yao Tang; Yuqian Jiang (Food Chemistry, 2026)

Screening potential antagonistic strains against tobacco bacterial wilt and evaluating the colonization ability of Bacillus velezensis TS08 - Fang Chen; Yinglong Liu; Pengfei He; Pengbo He; Yixin Wu; Ayesha Ahmed; Guowen Tang; Yining Di; Ping Tang; Yueqiu He; Shahzad Munir (Physiological and Molecular Plant Pathology, 2026)

Systemic immune evasion and tissue damage underlie the covert pathogenicity of Aeromonas veronii in endangered sturgeons - Jiachen Zhou; Dike Peng; Yuanyuan Tang; Haoyang Liu; Yining Chen; Ye Zhang; Yacheng Hu; Yuanjin Yang; Huifeng Dang; Jianan Xu; Yueping Zheng; Dan Xu (Aquaculture, 2026)

Elemental geochemical constraints on paleoprecipitation in westerlies‐dominated arid Asia: A comparative surface soil study from NE Iran and SW Tajikistan - Jiamei Lei; Qiang Wang; Yining Tang; Jia Jia; Xiangfeng Tang; Yongqiu Wu; Mi Wang; Davlatkhudzha Murodov; Farhad Khormali; Xin Wang (Journal of Quaternary Science, 2026)
Westerlies‐dominated arid Asia spans the dry mid‐latitude Asian interior from NE Iran across the Central Asian interior to NW China and the southern Mongolian Plateau. Although elemental geochemical proxies are widely used in monsoonal Asia, their applicability to loess deposits in this broader arid domain remains insufficiently tested, especially in its western and central sectors. Here, we investigate the geochemical characteristics of modern surface soils (0–2 cm) from the Iranian Loess Plateau and SW Tajikistan to evaluate their relationships with present‐day climatic conditions and their implications for paleoclimatic reconstruction. Specifically, we aim to (i) characterize elemental geochemical parameters and their paleoclimatic significance and (ii) identify robust proxies for paleoprecipitation reconstruction. Our results indicate (i) low chemical weathering intensity in both regions; (ii) a coupled influence of provenance and climate on weathering processes; and (iii) in NE Iran, strong relationships between the mean annual precipitation and the indices C [(Fe + Al + Mn + Cr + Co + Ni)/(Ca + Mg + Na + K + Sr + Ba)] ( r = 0.73, p r = 0.72, p 2 O + Na 2 O)/(Fe 2 O 3 + MnO 2 )] ( r = −0.71, p

Rhodotorula mucilaginosa SY-AN-9 as a novel starter culture for improving the safety of Northeastern Chinese dried sausage: Mitigating N-nitrosamines and elucidating the underlying mechanism - Ying Yue; Xu Yan; Siqi Zhang; Yining Tang; Wei Ji; Chaofan Ji; Yiwei Dai; Beiwei Zhu; Xinping Lin (Food Chemistry, 2026)

Subsurface Geological Image Augmentation: A Mathematical Morphology Method - Yining Huang; Ademide O. Mabadeje; Hewei Tang; Michael J. Pyrcz (Mathematical Geosciences, 2026)
Deep learning has transformed image analysis across scientific domains, but its application in geosciences remains limited by scarce training data. Traditional image augmentation techniques, such as translation, rotation, and flipping, fail to capture the complexity and range of subsurface geological feature configurations. Here, we demonstrate that mathematical morphology-based image augmentation significantly improves the performance of deep learning models in data-limited subsurface geological applications, achieving an $$R^2$$ R 2 of 0.97 compared to 0.84 for standard augmentation methods, with as few as four original training images. Our approach systematically transforms images by mimicking the natural variability of subsurface geological structures, enabling models to learn subsurface-specific invariants rather than merely being location- and orientation-independent. This novel method addresses a fundamental challenge in geoscientific machine learning, where high data acquisition costs have historically restricted model development. By generating geologically plausible synthetic training examples, our method enables robust subsurface geological characterization with minimal original data. Validated on synthetic pore/channel images, this morphology-based augmentation strategy demonstrates potential for extension to other deep learning-based subsurface characterization tasks in resource exploration and development applications.

Single-nucleus RNA sequencing reveals adipocyte lineage relationships and differentiation trajectory between intramuscular and intermuscular fat tissues of rainbow trout - Ming Huang; Xiangbing Zeng; Yuan Yao; Jinghong He; Wenxin Jiang; Yining Yu; Qingkai Tang; Qinfeng Gao; Yuan Tian (Aquaculture, 2026)

Reduction of N-nitrosodimethylamine in fermented cooked sausages by combined treatment of Lactiplantibacillus pentosus R3 and tea polyphenols - Yining Xu; Lianxu Tang; Junwei Gao; Qiong Pan; Baocai Xu; Huiting Luo; Peijun Li (Food Control, 2026)

Improving plot-level wheat yield prediction by integrating proximal-sensed spike photosynthetic phenotyping into crop growth model - Haiyu Tao; Yining Tang; Jiaoyang He; Caili Guo; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Field Crops Research, 2026)

The effect of thermal expectation on occupants’ response to moderate temperature ramp up: A controlled chamber experiment - Tianning Shao; Shiming Chen; Yining Lu; Yixin Tang; Shuaichen Ge; Xinyue Li; Wu Deng; Zhiang Zhang; Jingjing Shao; Tongyu Zhou (Building and Environment, 2026)

Potential risk signals for drug-related osteomyelitis: a comprehensive disproportionality analysis based on the FDA Adverse Event Reporting System (FAERS) database - Duoqin Huang; Liulin Fu; Yining Wang; Kang Zou; Ronghua Zou; Yuquan Tang; Zhen Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

MXene-supported MOF-derived multicore ZrSe2@MnSe2 complex structure for high-rate and long-cycle-life supercapacitors - Yuhan Cui; Jing Sun; Yining Wang; Lijie Zhao; Yanjie Lv; Yuzhe Tang; Wenxi Zhang; Zhongmin Su (Fuel, 2026)

Novel Metabolomic and Adiposity Markers Improve Prediction of Obstructive Sleep Apnea: A Prospective Analysis in the China Human Phenobank - Yudan Wu; Yihan Ba; Chen Chen; Qi Wang; Qinsheng Chen; Jinxian Zhang; Longlong Chen; Yining Zhao; Biru Shi; Lisong Ye; Wei Chen; Chengyan Wang; et al. (Phenomics, 2026)

Novel insight into the heavy metal immobilization by coal fly ash-based geopolymers using machine learning and density functional theory - Kaizhi Yang; Bo Yang; Kezhou Yan; Yining Su; Longyi Zhao; Jungang Tang; Yu Che; Yanxia Guo (Waste Management, 2025)

Integrating computer vision and machine learning technologies for model building to quantify intermuscular fat content in salmonid fillets - Ming Huang; Libo Wang; Boyuan Wang; Wenxin Jiang; Yining Yu; Qingkai Tang; Qinfeng Gao; Yuan Tian (Food Control, 2025)

Preparation and properties of esterified starch-based antimicrobial sustained-release indicator films - YiNing Xu; Cheng Tang; Peng Zhang; YingLan Yuan; ShiYan Zhou; JinMing Wan; Zhihe Qing; Qi-Jie Chen (Food Research International, 2025)

How aging microplastics influence heavy metal environmental fate and bioavailability: A systematic review - Qian Wang; Yining Gao; Xiaoyan Tang; Zhuanling Yang; Liang Tang; Guangjie Luo; Chengshuai Liu; Hui Tong (Environmental Research, 2025)

Landscapes of alternative splicing genes/events in the gills of Mozambique tilapia (Oreochromis mossambicus) and their roles in high-salinity adaptation - Ming Huang; Han Yu; Boyuan Wang; Wenxin Jiang; Na Xue; Hancheng Bao; Yining Yu; Qingkai Tang; Qinfeng Gao; Yuan Tian (Aquaculture International, 2025)

Estimating wheat partitioning coefficient using remote sensing and its coupling with a crop growth model - Yining Tang; Yuanyuan Pan; Yuejiao Zhao; Xin Li; Jiaoyang He; Caili Guo; Hengbiao Zheng; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Field Crops Research, 2024)

Characterizing identity by descent segments in Chinese interpopulation unrelated individual pairs - Qiqi Ji; Yining Yao; Zhimin Li; Zhihan Zhou; Jinglei Qian; Qiqun Tang; Jianhui Xie (Molecular Genetics and Genomics, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

Improving the estimation accuracy of wheat maturity date by coupling WheatGrow with satellite images - Yanxi Zhao; Zhihao Zhang; Yining Tang; Caili Guo; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (European Journal of Agronomy, 2024)

Spatio-temporal change of winter wheat yield and its quantitative responses to compound frost-dry events – An example of the Huang-Huai-Hai Plain of China from 2001 to 2020 - Yanxi Zhao; Liujun Xiao; Yining Tang; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Science of The Total Environment, 2024)

Diagnostic and prognostic performance of artificial intelligence-based fully-automated on-site CT-FFR in patients with CAD - Bangjun Guo; Mengchun Jiang; Xiang Guo; Chunxiang Tang; Jian Zhong; Mengjie Lu; Chunyu Liu; Xiaolei Zhang; Hongyan Qiao; Fan Zhou; Pengpeng Xu; Yi Xue; et al. (Science Bulletin, 2024)

Non-targeted metabolomics provides insights into the distinct amino acid and lipid metabolism in liver tissues of rainbow trout (Oncorhynchus mykiss) cultured in seawater at different temperatures - Yuan Tian; Wen Wang; Wenxin Jiang; Gong Zhang; Jinghong He; Shuanglin Dong; Yangen Zhou; Wenzhao Yang; Qingkai Tang; Yining Yu; Qinfeng Gao (Aquaculture, 2024)

Estimating wheat grain yield by assimilating phenology and LAI with the WheatGrow model based on theoretical uncertainty of remotely sensed observation - Yining Tang; Ruiheng Zhou; Ping He; Minglei Yu; Hengbiao Zheng; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Agricultural and Forest Meteorology, 2023)

Improving microbiological and physicochemical properties of fresh-cut apples using carvacrol emulsions - Qi Guo; Yudie Qing; Liyue Qiang; Gengan Du; Kehan Shi; Jiayao Tang; Xiaohai Yan; Hong Chen; Yuan Yue; Yining He; Yahong Yuan; Tianli Yue (Food Bioscience, 2023)

Plant Hormone Metabolome and Transcriptome Analysis of Dwarf and Wild-type Banana - Biao Deng; Xuan Wang; Xing Long; Ren Fang; Shuangyun Zhou; Ji Zhang; Xiaolu Peng; Zhenyu An; Weixiong Huang; Wenzhong Tang; Yining Gao; Jinyan Yao (Journal of Plant Growth Regulation, 2022)
Gibberellin (GA), auxin (IAA) and brassinosteroid (BR) are indispensable in the process of plant growth and development. Currently, research on the regulatory mechanism of phytohormones in banana dwarfism is mainly focused on GA, and few studies are focused on IAA and BR. In this study, we measured the contents of endogenous GA, IAA and BR and compared the transcriptomes of wild-type Williams banana and its dwarf mutant across five successive growth periods. We investigated the relationship between hormones and banana dwarfism and explored differential gene expression through transcriptome analysis, thus revealing the possible metabolic regulatory mechanism. We inferred a complex regulatory network of banana dwarfing. In terms of endogenous hormone levels, GA and IAA had significant effects on banana dwarfing, while BR had little effect. The key gene in GA biosynthesis of is GA2ox , and the key genes in IAA biosynthesis are TDC and YUCCA . The differential expression of these genes might be the main factor affecting hormone levels and plant height. In terms of hormone signal transduction, DELLA and AUX/IAA repressor proteins were the core regulators of GA and IAA, respectively. They inhibited the process of signal transduction and had feedback regulation on hormone levels. Finally, the transporter protein PIN, AUX1/LAX protein family and ABCB subfamily played supplementary roles in the transport of IAA. These results provide new insights into GA and IAA regulation of banana growth and a reliable foundation for the improvement of dwarf varieties.

The adsorption mechanism of CF4 on the surface of activated carbon made from peat and modified by Cu - Rong Pan; Wei Dong; Yanni Guo; Yining Tang; Jun Shang; Lei Zhou; Deliang He (Environmental Science and Pollution Research, 2022)

New curtachalasin from the Xylaria sp. DO 1801 - Jia Wang; Yining Sang; Siqi Tang; Peng Zhang (Natural Product Research, 2021)

Head-to-head comparison of the diagnostic accuracy of Xpert MTB/RIF and Xpert MTB/RIF Ultra for tuberculosis: a meta-analysis - Jianjun Jiang; Jin Yang; Yining Shi; Yongmei Jin; Sihui Tang; Na Zhang; Youjin Lu; Gengyun Sun (Infectious Diseases, 2020)

Environmentally persistent free radicals in PM2.5: a review - Mengxia Xu; Tao Wu; Yu-Ting Tang; Tong Chen; Lavrent Khachatryan; Poornima Ramesh Iyer; Dengting Guo; Anran Chen; Miao Lyu; Jinhu Li; Jiaqi Liu; Dan Li; et al. (Waste Disposal & Sustainable Energy, 2019)

Adsorption of Ni2+ and Pb2+ from water using diethylenetriamine-grafted Spirodela polyrhiza: behavior and mechanism studies - Wei Qu; Deliang He; Yanni Guo; Yining Tang; Jun Shang; Lei Zhou; Rilong Zhu; Ren-Jie Song (Environmental Science and Pollution Research, 2019)

Characterization of modified Alternanthera philoxeroides by diethylenetriamine and its application in the adsorption of copper(II) ions in aqueous solution - Wei Qu; Deliang He; Yanni Guo; Yining Tang; Ren-Jie Song (Environmental Science and Pollution Research, 2019)